The Analysis of Figurative Language Used in 'Still I Rise' Poem by Maya Angelou - Nur, Muhammad Rauuf Oktavian; Miranti, Ririt Rachma (Universitas Muhammadiyah Surakarta, 2018)
This study aimed to find out the kinds of figurative language in the selected poetry of Maya Angelou, entitled Still I Rise. The focus of this study is figurative language which involves: Metaphor, Personification, Hyperbole, Simile, Metonymy, Synecdoche, Irony, Antithesis, Symbolism, and Paradox. Qualitative approach with design of content analysis was used in this study. The researcher acted as the main instrument since he was the one who analyzed the figurative language. Moreover checklist was also used to support his data collection. The data was analyzed through three stages; 1). Data reduction, 2). Data representation, 3). Conclusion. The result of his study showed there were 14 sentences that containing figurative language in Still I Rise Poetry of Maya Angelou. They were; Metaphor (7 sentences), Personification (1 sentence), and Simile (6 sentences). The researcher conclude, if the figurative language used by Angelou to compare, or even symbolize the sentences to bring the meaning come up with beautiful language. Mostly of her poetries told about her experience in the past that rooted to history of the discrimination of American-African.